Voltage-gated calcium channel autoimmune cerebellar degeneration: Case and study of cytotoxicity - McKasson, Marilyn (Neurol Neuroimmunol Neuroinflamm, 2016)
OBJECTIVES: To describe response to treatment in a patient with autoantibodies against voltage-gated calcium channels (VGCCs) who presented with autoimmune cerebellar degeneration and subsequently developed Lambert-Eaton myasthenic syndrome (LEMS), and to study the effect of the patient's autoantibodies on Purkinje cells in rat cerebellar slice cultures. METHODS: Case report and study of rat cerebellar slice cultures incubated with patient VGCC autoantibodies. RESULTS: A 53-year-old man developed progressive incoordination with ataxic speech. Laboratory evaluation revealed VGCC autoantibodies without other antineuronal autoantibodies. Whole-body PET scans 6 and 12 months after presentation detected no malignancy. The patient improved significantly with IV immunoglobulin G (IgG), prednisone, and mycophenolate mofetil, but worsened after IV IgG was halted secondary to aseptic meningitis. He subsequently developed weakness with electrodiagnostic evidence of LEMS. The patient's IgG bound to Purkinje cells in rat cerebellar slice cultures, followed by neuronal death. Reactivity of the patient's autoantibodies with VGCCs was confirmed by blocking studies with defined VGCC antibodies. CONCLUSIONS: Autoimmune cerebellar degeneration associated with VGCC autoantibodies may precede onset of LEMS and may improve with immunosuppressive treatment. Binding of anti-VGCC antibodies to Purkinje cells in cerebellar slice cultures may be followed by cell death. Patients with anti-VGCC autoantibodies may be at risk of irreversible neurologic injury over time, and treatment should be initiated early.